RSSI-based physical instrusion alarm and indoor automation system - Rafhanah Shazwani binti Rosli (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
In recent years, the Internet of Things technology has advanced rapidly across the technological world. One of the unique applications under the domain of Internet of Things is an integrated physical intrusion alarm and indoor automation system based on Received Signal Strength Indicator values as proposed and developed in this thesis. Existing solutions rely heavily on network protocols which build on single expensive hardware dedicated solely for a single implementation; thus, it is inefficient in terms of cost and hardware. On the contrary, the innovation of this thesis depends on the existing network infrastructure. It efficiently harvests the radio frequency energy available from a cheap transmitter pre-installed in the local indoor setting. Furthermore, it is implemented using an integrated module consisting of off-the-shelves electronics with the minimum number of hardware. The system detects intrusion based on the analysis of interferences in Received Signal Strength Indicator readings that are affected by human crossings at the Line of Sight between the main device and nodes of the system; Nevertheless, only a few minutes of offline training phase is required, then the system is ready to operate with high accuracy. Whenever the system detects an intrusion where a crossing of an unknown human subject is detected, it will trigger an alarm and automate the system of any circuit connected to it. In addition, the system is integrated with a mobile application interface as a mechanism of intrusion alarm and for the ease of access to the intrusion detection log. Above all, the viability of the system developed was investigated through a series of experiments which were done in two parts. The first part is the characteristic analysis of the design parameters involved in the system. Once the design parameters were analysed and the proper parameter value was chosen for the system, the second part of analysis which is the performance of the system was conducted. The experiment was conducted in an indoor setting environment which is an office room of a laboratory in a University building. It involves 10 different human test subjects with a variety of body dimensions. The test subjects were made to cross the Line of Sight between the main device and nodes four times. The outcomes have shown that the sensitivity, which is the ability of the system to detect the crossing of unregistered subjects as an intrusion is averaging at 93.33%. Specificity, that is the ability of the system to detect the crossing of only unregistered subjects as an intrusion, is on average at an optimum level of 100%. Accuracy or the degree to which the system detects an intrusion correctly is averaging at 94%. The invention is highly competitive and offers various solutions to different areas of homes and industries. A survey conducted on 150 potential consumers shows that the majority are looking forward to using the system device in their daily lives. In a nutshell, this thesis has produced a novel RSSI-based physical intrusion alarm and indoor automation system along with its market-ready device prototype.